2017
DOI: 10.4328/jcam.4707
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Preincisional and Postincisional 0.25% Levobupivacaine Infiltration in Thyroid Surgery

Abstract: Boyun cerrahisinde analjezi amaçlı yara yerinin lokal anestezik ile infiltrasyonu konusuna literatürde yeterince yer verilmemiştir. Gereç ve Yöntem: Tiroid cerrahisi planlanan 60 hasta rastgele iki gruba ayrıldı. Grup 1'de insizyon öncesi Grup 2'de cerrahi bitiminde yara yerine %0.25'lik levobupivakain uygulandı. Hastalar postoperatif dönemde ağrı ve yan etkiler açısından 24 saat takip edildi. İntraoperatif ve postoperatif opioid tüketimi, ilk analjezik gereksinim zamanı kaydedildi. 24 saat sonunda hasta memnu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Of the 17 studies, seven (Teksoz et al, Choi et al, Miu et al, Kang et al, Kesisoglou et al, Ekinci et al, and Ahiskalioglu et al) reported statistically significant decreases in VAS and NRS postoperative pain scores. 23,25,27,28,35,36,40 Teksoz et al found lower VAS scores at 30 minutes, 1 hour, and at 8 hour postoperatively ( P = .03, P = .04, P = .005, respectively). 23 Kesisoglou similarly reported significantly decreased VAS scores at 0, 3, 6, 9, 12, and 24 hours after surgery ( P < .05).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Of the 17 studies, seven (Teksoz et al, Choi et al, Miu et al, Kang et al, Kesisoglou et al, Ekinci et al, and Ahiskalioglu et al) reported statistically significant decreases in VAS and NRS postoperative pain scores. 23,25,27,28,35,36,40 Teksoz et al found lower VAS scores at 30 minutes, 1 hour, and at 8 hour postoperatively ( P = .03, P = .04, P = .005, respectively). 23 Kesisoglou similarly reported significantly decreased VAS scores at 0, 3, 6, 9, 12, and 24 hours after surgery ( P < .05).…”
Section: Resultsmentioning
confidence: 94%
“…The total amount of PCA consumption (10 mg/mL meperidine) also did not differ significantly ( P > .05). 33 In regards to rescue analgesic medications, four studies (Kang et al 28 [Fentanyl: 510.75 μg vs 422.50 μg; P < .05], Choi et al 25 [Fentanyl: 550.79 ± 46.46 μg vs 598.57 ± 55.58 μg; P < .01], Karthikeyan et al 31 [Morphine PCA: 30.70 ± 4.77 mg vs 0.85 ± 3.95 mg; P = .001], and Ekinci et al 36 [Tramadol: 72.4 ± 24.5 mg vs 91.5 ± 36.8 mg; P = .027]) reported statistically significant decreases in need for additional medication. Eight studies compared bilateral superficial cervical plexus block (BSCPB) encompassing 274 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen articles published between 1994 and April 2023 were identified [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Table 1 summarizes the reported trials.…”
Section: Methodsmentioning
confidence: 99%